Pengaruh Strategi Pembelajaran Heuristic Vee Terhadap Pemahaman Konsep Matematis Peserta Didik - Rahmawati, Riska; Masykur, Rubhan; Fadila, Abi (Desimal: Jurnal Matematika, 2018)
The ability to understand the mathematical concepts of learners is important. However, some existing research suggests that understanding of the mathematical concepts of learners is still low. The low understanding of the mathematical concepts of learners is allegedly caused because students are still difficult in solving math problems and less active in the process of learning in class. The implementation of the heuristic vee expenditure strategy is expected to improve the problem. The purpose of this study is to determine the effect of heuristic vee learning strategy on the ability to understand the mathematical concepts of learners. This research type used Quasi-Experiment Design research and sampling technique used is Probability Sampling method with Random Sampling technique. Hypothesis test used in this research is the t-test. The result of statistical test shows that the value of t_hitung based on the calculation obtained t_hitung = 2.096, and t_table = 1.998 so t_hitung>t_table, with a real level of 0.05, in other words, it can be concluded that the students' mathematical concept understanding that expected heuristic vee learning strategy better from the conceptual comprehension ability applied by the lecture method.